Village Government Towards the Developing Village Index (Study in Banten Province) - Fartini, Ade; Nugraha, David; Sudira, Ahamad (Al Ahkam, 2024)
Village government policies based on Village Law Number 6 of 2014 and the idea behind the developing village index (IDM) program are further explained in the Village Minister Regulation (Permendes) No. 2 of 2016 which focuses on village development patterns and maps In Article 3, it is stated that the concept of IDM is derived from several categories, including the economic resilience index (IKE), which measures economic strength, the environmental resilience index (IKL) for assessing environmental sustainability, and the social resilience index (IKS) to evaluate community well-being. The central government's policy with village funds through the State Budget is an effort to realize village development through the economy, welfare and village independence. Both the village government and community participation are crucial in enhancing the value of the Developing Village Index.The research method uses a qualitative method with descriptive interpretation which aims to obtain an overview to examine and explain the potential of village funds for village development and explain the value of the Developing Village Index as well as the recommendations produced to encourage Cimangeuteung Village, Tegalongok Village and Bumijaya Village in Banten Province to increase their development from a developing village to a developed village. Transparency of village government policies, strong governance of village bureaucratic administration, and active participation of village communities are crucial for village development.In order to achieve a good and advanced village government